Fenton-like degradation of 2, 4-dichlorophenol using calcium peroxide particles: performance and mechanisms. Issue 8 (16th January 2017) - Wang, Hefei; Zhao, Yongsheng; Su, Yan; Li, Tianyi; Yao, Meng; Qin, Chuanyu
Abstract : H2 O2 was slowly released from CaO2 particle dissolution and then decomposed into radicals to degrade 2, 4-dichlorophenol at a moderate rate. Abstract : The degradation process of 2, 4-dichlorophenol (2, 4-DCP) in aqueous solution by a Fenton-like system using calcium peroxide (CaO2 ) particles as a source of solid H2 O2 was investigated. EDTA was added to the system to chelate iron and promote the Fenton-like reaction. The results show that 2, 4-DCP can be readily degraded in a CaO2 /EDTA-chelated Fe(ii ) system. Compared with an H2 O2 /EDTA-chelated Fe(ii ) system, 2, 4-DCP degradation showed a moderate reaction rate owing to the slow dissolution process of the CaO2 particle. Complicated degradation kinetics were observed and the possible reason was revealed. The initial amount of EDTA chelated iron lost during the Fenton-like reaction was in the range 20–30%. The effects of different reaction parameters, such as initial pH, CaO2 dosage and amount of EDTA–chelated iron, on 2, 4-DCP degradation were studied. According to the identification of dominant reactive species and degradation intermediates, a possible theoretical degradation pathway of 2, 4-DCP was proposed.